2005
DOI: 10.1159/000085741
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Atypical Pathogens among Community-Acquired Pneumonia Adult Patients Admitted to Hospital in Kuwait

Abstract: Objectives: The aim of this study is to determine the microbial etiology and severity of community-acquired pneumonia (CAP) in Kuwait. Subjects and Methods: The severity of consecutive adult CAP cases admitted to 3 hospitals over a 1-year period was classified according to the Pneumonia Outcome Research Team (PORT) severity index. The microbial etiology was determined using standard methods for bacteria and serological tests for atypical and viral pathogens. Results: The study population was 124 of the 135 adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Atypical organisms such as Chlamydia pneumoniae, Mycoplasma pneumoniae and Legionella pneumophila are prevalent in the Middle East and have a significant role in the aetiology of CAP. 58 Al-Ali et al in a study from Jordan, reported that C. pneumoniae and My. pneumoniae were the leading pathogens of pneumonia in children (incidences 14% and 6% respectively).…”
Section: Atypical Organismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Atypical organisms such as Chlamydia pneumoniae, Mycoplasma pneumoniae and Legionella pneumophila are prevalent in the Middle East and have a significant role in the aetiology of CAP. 58 Al-Ali et al in a study from Jordan, reported that C. pneumoniae and My. pneumoniae were the leading pathogens of pneumonia in children (incidences 14% and 6% respectively).…”
Section: Atypical Organismsmentioning
confidence: 98%
“…Atypical organisms such as Chlamydia pneumoniae , Mycoplasma pneumoniae and Legionella pneumophila are prevalent in the Middle East and have a significant role in the aetiology of CAP 58 . Al‐Ali et al .…”
Section: Pulmonary Pathology In the Middle Eastmentioning
confidence: 99%
“…However, influenza-associated mortality represents only the ‘tip’ of the iceberg, since a consistently larger number of persons infected with influenza virus exhibit self-limited, uncomplicated, acute febrile respiratory symptoms. Globally, both ‘mild’ and ‘severe’ influenza cases account for several billions of days of illness each year, hundreds of millions of days of work lost and millions of hospitalizations that have to be added to the list of costs attributable to influenza [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research related to Legionella is scarce [1820]. Furthermore, no reports are available on the current status of the prevalence of Legionnaires' disease and associated cases in Kuwait.…”
Section: Introductionmentioning
confidence: 99%